Defending White Scientific Masculinity: THE FBI, THE MEDIA AND PROFILING TACTICS DURING THE POST-9/11 ANTHRAX INVESTIGATION. Issue 1 (2nd January 2016) - D'Arcangelis, Gwen
Abstract: While many feminist and postcolonial scholars have analyzed the post-9/11 politic in the United States, few have focused on the anthrax "attacks" that followed the 11 September 2001 World Trade Center disaster. The FBI search for the perpetrator of the 2001 anthrax mailings was an important node in US national security discourse making – it culminated in the fingering of a white male government biodefense scientist and cast doubt on the role of scientific expertise in provisioning national security. This article argues that while "white scientific masculinity" was put into question, it was simultaneously shored up as a nationalist symbol of protection against bioterrorism. This article traces shifts across the three FBI-led profiles of the anthrax perpetrator, along with concomitant news media coverage: the white male "loner" nonscientist, the white male "loner" amateur scientist and finally the white male biodefense scientist. Using a cultural studies approach, this article details how at each successive investigatory stage profilers mobilized hegemonic discourses to re-instantiate the authoritative status of white scientific masculinity in US national security. This analysis offers an important dimension to feminist and postcolonial critiques of the symbolic and institutional investment in white masculinity during the War on Terror.